Environmental Performance Review: Romania - United Nations Economic Commission for Europe (United Nations, 2022)
This third EPR of Romania takes stock of progress made by the country in the management of its environment since its second review in 2012 and assesses the implementation of the recommendations of the previous EPR. The review covers legal and policy frameworks and compliance assurance mechanisms. It also focuses on greening the economy, environmental monitoring, public participation, and education for sustainable development. It includes a substantive analysis of the country’s participation in and commitments to international agreements, as well as its climate change adaptation and mitigation measures. Furthermore, the EPR addresses issues of specific importance to Romania related to air protection, water management, waste and chemicals management, and biodiversity and protected areas. Finally, the review includes in all chapters an assessment of relevant targets of the Agenda 2030 as well as recommendations related to the achievement of the Sustainable Development Goals. The publication is aimed at officials and experts working for public authorities responsible for environmental policy, representatives of civil society, the business community, academia, and the media. The Environmental Performance Review (EPR) Programme is an important instrument for countries with economies in transition. Third-cycle EPRs focus on environmental governance and financing in a green economy context, countries’ cooperation with the international community, and environmental mainstreaming in priority sectors. Through the peer review process, EPRs also promote dialogue among ECE member countries and harmonization of environmental conditions and policies throughout the region.